Numerical modelling of plasma production with radio-frequency heating using four-strap π-phased antenna - Kulyk, Yu.S.; Moiseenko, V.Е.; Wauters, T.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2014)
Results of calculations of radio-frequency (RF) plasma production in the ion-cyclotron range of frequencies (ICRF) in the Uragan-2M stellarator using four-strap π-phased antenna are presented. The analysis carried out with usage of a self-consistent model that simulates plasma production with ICRF antennas.